2019
DOI: 10.1590/1809-43412019v16d553
|View full text |Cite
|
Sign up to set email alerts
|

On the way: Technique, movement and rhythm in the training of guide dogs

Abstract: In the article I present an ethnographic reflection on the process of guide dogs generation, an animal assistive technology developed to facilitate the mobility of the visually impaired person. Focusing especially on the training phase, I try to understand the trajectory of transformations, the unfolding of events and the changes of movement that make certain dogs able to "graduate" as guides. Following a Maussian perspective, the guiding technique is understood here as the result of a certain relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Through its channel pass information, forces and laws. In a cord can be found all the objective and collective attributes of Hermes (Serres, [2014(Serres, [ ]1995d. [….]…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Through its channel pass information, forces and laws. In a cord can be found all the objective and collective attributes of Hermes (Serres, [2014(Serres, [ ]1995d. [….]…”
Section: Notesmentioning
confidence: 99%
“…1 The reason for my choice is twofold. First, it is related to an ongoing interest in the role of non-humans in the construction of our social fabric, and in the possible invention of a new political ecology where those who (or which) have long been misrepresented or not represented at all could be given a voice (Serres, 2014;Latour, 1993Latour, , 2005Hache and Latour, 2010;Houdard and Thiery, 2011;Hache, 2012). Non-humans, in the context of my study, are not only machines, technics, or objects; but they are also animals (Haraway, 2003(Haraway, , 2007Despret, 2004, 2006, Despret and Buchanan, 2016Doré and Michalon, 2017).…”
mentioning
confidence: 99%
“…Guide dogs are expected to perform, on average, 50 tasks for their vision impaired human partners (Mouret 2019;von der Weid 2019;Putnam 1954). Simultaneously, they are required to remain calm and focused amidst distracting or stressful environments (Berentzen 2016;Putnam 1954).…”
Section: Introductionmentioning
confidence: 99%
“…Though anecdotal, it has also been suggested that the use of face masks may pose unique communication challenges for guide dog users by muffling the vocalization of handlers when commands are being communicated [ 29 , 30 ]. Although guide dogs are not trained to rely on facial expressions and instead rely on a combination of verbal and physical commands [ 31 , 32 ], it is known that dogs read subtle muscle changes that indicate a twitch or a smile, which may facilitate communication [ 29 , 33 ]. The inability to use echolocation is especially concerning, as individuals with visual impairments are less able to rely on alternative options, such as the use of sighted guides and volunteers during the pandemic, due to physical distancing measures [ 3 , 5 , 26 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%